Behaviour of filled joint under shear loading - Ong, Heng Yau (2006)
In tropical country like Malaysia, hot and wet weather encourages the formation of filled joint, which is one of the most critical discontinuities that affect the stability of rock mass. It is therefore essential to study the characteristics and behaviours of filled joint to understand their effect on rock mass. Filled joint resulting from in situ deposition of infilling in the joint aperture was the main focus of this study. Dominant components of this filled joint were identified and accordingly modeled in the laboratory tests. A large shear box apparatus (300mm square section) has been designed and fabricated specifically to simulate the loading configurations on the filled joint model. Cast concrete of different surface roughness (planar to rough) was used as joint block. Joint aperture was filled with actual infill material, with thickness between 5 to 15 mm (average density before shear of approximately 1800 kg/m3). The normal stress applied during shear was between 130 to 370 kPa, equivalent to typical slope height of 5 to 15 m. The study showed that the shear resistance of rough filled joint reduces with increasing infill thickness and eventually approaches the shear strength of the infill material. Infill thickness has no significant effect on the shear strength of filled joint with smooth surface texture as its shear strength is almost similar to that of the infill. Nevertheless, with very thin infill (approximately thickness of an infill particle) in smooth joint, the resultant shear resistance is much lower than that of the infill. This implies that the weakest shear plane of a filled joint might not lie within the infill, but at the interface between infill and joint surface. Crushing of infill particles has been noted to influence the shear and compressive behaviours of filled joint